Tingkat Kecemasan Narapidana Wanita di Lapas Kendari dengan Kuesioner Taylor Manifest Anxiety Scale (TMAS) - Indriono Hadi; Lilin Rosyanti; Nur Sri Afrianty (Poltekkes Kemenkes Kendari, 2018)
When a woman is imprisoned, she will experience a lot of pressure. Prisons create feelings of fear and unpleasant feelings due to bad assumptions and pressures experienced such as beatings, torture, sexual harassment, poor health and very minimal facilities, besides that there is a stigma that will remain attached to someone when they are out of prison. The length of their sentence and isolation from the outside environment has a considerable psychological impact on the mental health of prisoners. The purpose of this study was to determine the anxiety level of female prisoners in prison using the Taylor Manifest Anxiety Scale (TMAS) Questionnaire. The sample in this study were all 30 female prisoners in prison. Using the descriptive approach method carried out in May-June 2016. The characteristics of respondents with the highest age were 26-35 years (50%), most of the respondents have formal education in SMA (53.33%), and have marriage (87%). The cause of imprisoned is drug usage (70%). The mean and deviation standard of the level of anxiety of female prisoners in prison are moderate anxiety (22.93 ± 3.58), severe anxiety (29.20 ± 5.52) and average mild anxiety (14 , 60 ± 1.14). This is importance for nurses and prison staff to give attention to the anxiety level of women in prison to prevent physical and psychological problems.